Daniel Dennett - Brook, Andrew; Ross, Don, 1962- (U.K : Cambridge University Press, 2002)
Publisher Description (unedited publisher data) Contemporary Philosophy in Focus will offer a series of introductory volumes to many of the dominant philosophical thinkers of the current age. Each volume will consist of newly commissioned essays that will cover all the major contributions of a preeminent philosopher in a systematic and accessible manner. Author of such groundbreaking and influential books as Consciousness Explained and Darwin's Dangerous Idea, Daniel C. Dennett has reached a huge general and professional audience that extends way beyond the confines of academic philosophy. He has made significant contributions to the study of consciousness, the development of the child's mind, cognitive ethnology, explanation in the social sciences, artificial intelligence, and evolutionary theory. This volume is the only truly introductory collection that traces these connections, explores the implications of Dennett's work, and furnishes the non-specialist with a fully-rounded account of why Dennett is such an important voice on the philosophical scene
Dennett's position in the intellectual world / Andrew Brook and Don Ross -- The appearance of things / Andrew Brook -- Catching consciousness in a recurrent net / Paul M. Churchland -- The intentional stance : developmental and neurocognitive perspectives / Richard Griffin and Simon Baron-Cohen -- Dennett's contribution to research on the animal mind / Robert M. Seyarth and Dorothy L. Cheney -- Dennettian behavioural explanations and the roles of the social sciences / Don Ross -- That special something : Dennett on the making of minds and selves / Andy Clark -- A question of content / Kathleen Akins -- Dennett and artificial intelligence : on the same side, and if so, of what? / Yorick Wilks -- Dennett and the Darwin wars / Don Ross
Includes bibliographical references (pages 294-296) and index
Keywords: Dennett, D. C; Aufsatzsammlung